Odpowiedzi

2009-11-24T17:43:12+01:00
×=- 1 i y=0,1
a 4(5y+1)(1-5y)-5(4x+1)(1-4x)
b (x+2y)²+(2x-y)²-5(x-y)(x+y)
c 3y(3y-2×)-(3-x)(x+3)-(x-3y)²

a)4(5y-25y²+1-5y)-5(4x-16x²+1-4x)=
-100y²+4+80x²-5=
80x²-100y²-1=80*(-1)²-100*(0,1)²-1=
80-1-1=78

b)(x+2y)²+(2x-y)²-5(x-y)(x+y)=
x²+4xy+4y²+4x²-4xy+y²-5x²-5y²=
x²+4x²-5x²+4y²+y²-5y²+4xy-4xy=0

c)3y(3y-2×)-(3-x)(x+3)-(x-3y)²=
-6xy-(x-3y)²+9y²+x²-9=
-6xy-x²+6xy-y²+9y²+x²-9=
8y²-9=8*(0,1)²-9=8*0,01-9=-8,92

2009-11-24T18:06:38+01:00
A 4(5y+1)(1-5y)-5(4x+1)(1-4x)=4(1-25y²)-5(1-16x²)=4-100y²-5+80x²
b (x+2y)²+(2x-y)²-5(x-y)(x+y)=x²+4xy+4y²+4x²-4xy+y²-5(x²-y²)=
=x²+4xy+4y²+4x²-4xy+y²-5x²+5y²=10y²
c 3y(3y-2×)-(3-x)(x+3)-(x-3y)²=9y²-6xy-9+x²


a)4-100y²-5+80x²=-100(0,1)²-1+80(-1)²=1-1+80+1=81
b)10y²=10(0,1)²=0,1
c)9y²-6xy-9+x²=9(0,1)²-6(-1)(0,1)-9+(-1)²=0,09-0,06-9+1=0,03-8=
=7,97